2008
DOI: 10.1007/s11694-008-9055-z
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of toxigenic fungi using hyperspectral imagery

Abstract: Some pathogenic fungi, Aspergillus flavus for example, produce mycotoxins that can contaminate grain products including wheat and corn. The contaminated grain poses a threat to the health of both humans and animals. Therefore, from the perspective of food safety and protection, it is important to detect and identify the different toxin-producing fungi encountered in food production. Earlier studies examined various spectral-based, nondestructive methods for the detection of fungi and toxins. The present report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In earlier studies about using several optimal wavelengths to establish models, Yao et al separated five fungi by using only three bands [18], while Sun et al fitted growth curves for different kinds of fungi by characteristic wavelength in region of visible spectrum [7]. The authors pointed out that the characteristic wavelengths in visible region had good performance, because these wavelengths were associated with the variations of fungal color and texture during culture time.…”
Section: Optimal Wavelengths Svm Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies about using several optimal wavelengths to establish models, Yao et al separated five fungi by using only three bands [18], while Sun et al fitted growth curves for different kinds of fungi by characteristic wavelength in region of visible spectrum [7]. The authors pointed out that the characteristic wavelengths in visible region had good performance, because these wavelengths were associated with the variations of fungal color and texture during culture time.…”
Section: Optimal Wavelengths Svm Modelsmentioning
confidence: 99%
“…For example, there have been some publications that have reported the use of hyperspectral imaging to detect fungi plated on the culture medium. Yao et al identified five types of toxigenic fungi on day 5 of growth using a hyperspectral image, and all five fungi can be easily separated by only three wavelength bands (743, 458 and 541 nm) [18]. Jin et al classified toxigenic and atoxigenic A. flavus using a hyperspectral image under UV light and halogen light source [19].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, halogen and UV light sources were used, and it was found that the classification obtained under UV light was more accurate than under halogen light. Yao et al (2008) prepared toxigenic fungi for mold separation and revealed that two types of fungi could be classified using HSI. Fiore et al (2010) detected fungiinoculated maize kernels using Vis/NIR HSI with a spectral range of 400~1,000 nm in the reflectance mode, while Shahin and Symons (2011) used HSI for the detection of Fusarium in damaged maize kernels.…”
Section: Application In Grainsmentioning
confidence: 99%
“…Recently, as a more readily accessible imaging solution, a visible and nearinfrared (VNIR) hyperspectral imaging technique was developed for detection of Campylobacter and non-Campylobacter organisms grown in Petri dishes [8]. Similarly, VNIR hyperspectral imaging was studied for fungi detection [9].…”
Section: Introductionmentioning
confidence: 99%